Role extension in advanced ultrasound practice: A framework approach and case study. (February 2023) - Reeve, Ruth; Higginson, Antony; Ball, Christopher; Beable, Richard; Smith, Mike
Introduction: Role extension into novel areas of ultrasound practice can be challenging for health care professionals. Expansion into existing areas of advanced practice typically occurs using established processes and accredited training; however, in areas where there is no formal training, there can be a lack of support for how to develop new and progressive clinical roles. Topic Description: This article presents how the use of a framework approach for establishing areas of advanced practice can support individuals and departments with safely and successfully developing new roles in ultrasound. The authors illustrate this via the example of a gastrointestinal ultrasound role, developed in an NHS department. Discussion: The framework approach comprises three elements, each interdependent upon and inform each other: (A) Scope of practice, (B) Education and competency and (C) Governance. (A) Defines (and communicates) the role extension and area(s) of subsequent ultrasound imaging, interpretation and reporting. By identifying the why, how and what is required this informs (B) the education and assessment of competency for those taking on new roles or areas of expertise. (C) Is informed by (A) and is an ongoing process of quality assurance to safeguard high standards in clinical care. In supporting role extension, this approach can facilitate new workforce configurations, skill expansion and enable increasing service demands to be met. Summary: By defining and aligning the components of scope of practice, education/competency and governance, role development in ultrasound can be initiated and sustained. Role extension utilising this approach brings benefits for patients, clinicians and departments.